Factorial Structure and Cross-Cultural Invariance of the Parenting Stress Index-Short Form in Hong Kong and Thailand - Gao, Xiaozi; Lee, Kerry (Frontiers in Psychology, 2021)
With increasing attention on the role of parenting stress on family functioning and children’s development, one area that has been neglected is how such relations differ across cultures. Although sometimes viewed as homogeneous, Asian countries often have markedly different belief systems. Cross-cultural studies require instruments that have been validated in different socio-cultural contexts. The widely used parenting stress index-short form (PSI-SF) has been used in several locations. However, results regarding its factorial structure have been mixed. Furthermore, there are only a few cross-cultural comparison studies. This study examined the factorial structure of an abridged version of the PSI-SF with data from Hong Kong (N = 258) and Thailand (N = 190). Results from confirmatory factor analyses indicated that in both cultures, a three-factorial structure provides the best model fit. Furthermore, we found evidence for partial metric invariance, suggesting that the test scores can be compared directly. Tests for convergent and discriminant validity revealed that the three factors were correlated with parent general distress, authoritative, authoritarian, and permissive parenting behaviours in both cultures. These findings suggest that the abridged PSI-SF can provide meaningful comparison of parenting stress between Hong Kong and Thailand.